Seminal and histopathological alterations in bucks challenged with Mannheimia haemolytica serotype a2 and its LPS endotoxin - Azhar, Nur Amira; Paul, Bura Thlama; Abdullah Jesse, Faez Firdaus; Lim, Eric Teik Chung; Kamarulrizal, Mat Isa; Mohd Lila, Mohd Azmi (Springer, 2022)
Pneumonic mannheimiosis is a widespread respiratory bacterial disease of small ruminants caused by Mannheimia haemolytica serotype A2. The disease is known to affect the respiratory organs of infected animals, but its effect on other vital and reproductive organs has not been fully explored. Previous studies have demonstrated increased serum pro-inflammatory cytokine concentration post-challenge with M. haemolytica A2 and its LPS, indicating systemic inflammation in the host. This study determined the potential tissue changes and alterations of sperm parameters due to infection of M. haemolytica A2 and its LPS endotoxin. In this study, twelve experimental bucks were randomly assigned to three groups of four bucks each: group 1 (control group) were intranasally inoculated with 2 mL of PBS pH 7.0, group 2 received 2 mL of 1.2 × 109 CFU/mL M. haemolytica A2 intranasally, and group 3 received 2 mL of LPS extracted from 1.2 × 109 CFU/mL of M. haemolytica A2 intravenously. Semen samples were collected at pre-determined intervals using an electro-ejaculator and analysed immediately after collection. All experimental bucks were slaughtered via exsanguination on day 60 to collect their vital and reproductive organs at necropsy, and the samples were processed and analysed for histopathological changes. The current study has revealed that bucks challenged with M. haemolytica A2 and its LPS exhibited alterations in semen parameters such as motility, wave pattern, viability, and morphological abnormalities. Mild to moderate histopathological changes of the lung, liver, testis, epididymis, vas deferens, prostate, and lymph nodes were also observed in both challenged groups. Therefore, this study revealed the potential harmful effects of respiratory mannheimiosis on the reproductive organs of the infected bucks and sheds light on the expanse of systemic effects of this disease.